Flexible roll forming of an automotive component with variable depth. Issue 4 (1st October 2016) - Abeyrathna, Buddhika; Rolfe, Bernard; Pan, Libo; Ge, Rui; Weiss, Matthias
Abstract: The conventional roll-forming process is limited to components having a constant cross section, while the recently developed flexible roll forming (FRF) process allows the production of components in which the section varies over the length of the part; this permits optimisation in terms of strength and weight. There has been an uptake of FRF in the heavy vehicle industry for the production of long and high-strength structural parts, but passenger car bodies are more complex and generally parts require variations in width and also in depth. The widespread application of FRF in the automotive industry, therefore, requires the formation of components that have intricate variations in profile depth over the length of the part. In this work, the FRF of an automotive bumper section is analysed numerically using the commercial software package COPRA® FEA RF. A detailed analysis of the distribution and history of plastic strain in longitudinal, transverse and thickness directions is performed and related to the shape defects observed in the process. The analysis shows that when forming variable depth components, zones of compressive longitudinal strain exist, that lead to wrinkling defects. These can be reduced by applying additional flange contact during the operation.